Zoonotic Politics: The Impossible Bordering of the Leaky Boundaries of Species. (July 2022) - Cudworth, Erika; Hobden, Stephen
Zoonotic pandemics shine an uncomfortable light on how human lifeways facilitate the sharing of pathogens across species. Yet our lack of acknowledgement of our shared vulnerability with those non-human animals we raise or hunt to kill and eat, whose habitats we encroach upon and destroy, whose populations we undermine and threaten, has led us to the current human health crisis. The predominant political response to zoonotic pandemic has been bordering practices of surveillance, securitisation and bodily separation. These practices reflect intra-human and species hierarchies. They also fail to acknowledge the extent to which the boundaries of species are leaky, and are continually breached. A posthumanist zoonotic politics seeks not to attempt to border the leaky boundaries of species, but rather to insist on a re-ordering of species relations towards less exploitative and extractive ways of sharing the planet with the myriad creatures that constitute our world. Politique zoonotique : l'impossible confinement des espèces